2012
DOI: 10.1111/j.1582-4934.2012.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of phosphatidyl‐inositol‐3,5‐bisphosphate for acute lung injury in neonatal swine

Abstract: Hypoxemic respiratory failure of the neonatal organism involves increased acid sphingomyelinase (aSMase) activity and production of ceramide, a second messenger of a pro-inflammatory pathway that promotes increased vascular permeability, surfactant alterations and alveolar epithelial apoptosis. We comparatively assessed the benefits of topical aSMase inhibition by either imipramine (Imi) or phosphatidylinositol-3,5-bisphosphate (PIP2) when administered into the airways together with surfactant (S) for fortific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The addition of imipramine to the exogenous surfactant improved lung function and decreased leukocyte counts and interleukin concentrations in the lavage fluid (Von Bismarck et al, 2008 ). In a follow-up study, Preuss and co-workers also demonstrated that topical Asm inhibition by imipramine significantly improves several respiratory parameters and lung edema in a triple-hit lung injury model (Preuss et al, 2012 ). Taken together, these studies make a strong argument for the use of surfactant preparations fortified with an ASM inhibitor for the treatment of neonates with hypoxemic respiratory failure.…”
Section: Applications Of Amitriptyline In Asm-related Diseasesmentioning
confidence: 98%
“…The addition of imipramine to the exogenous surfactant improved lung function and decreased leukocyte counts and interleukin concentrations in the lavage fluid (Von Bismarck et al, 2008 ). In a follow-up study, Preuss and co-workers also demonstrated that topical Asm inhibition by imipramine significantly improves several respiratory parameters and lung edema in a triple-hit lung injury model (Preuss et al, 2012 ). Taken together, these studies make a strong argument for the use of surfactant preparations fortified with an ASM inhibitor for the treatment of neonates with hypoxemic respiratory failure.…”
Section: Applications Of Amitriptyline In Asm-related Diseasesmentioning
confidence: 98%
“…The authors speculate that, due to the high abundance of S-ASM from endothelial cells, injured lung capillary endothelial cells aggravate cellular damage in a vicious cycle, resulting in the sustained lung damage observed in patients despite smoking cessation. In a neonatal pigled model of pulmonary inflammation, S-ASM activity and ceramide concentration are reduced in serum after treatment of lungs with inhaled surfactant factor combined with the FIASMA imipramine (von Bismarck et al, 2008;Preuß et al, 2012).…”
Section: S-asm In Pulmonary Edemamentioning
confidence: 99%
“…Furthermore, acid sphingomyelinase (ASM), an enzyme generating ceramide, was increased in ovine BPD [25] and in septic patients, where it correlated with their mortality [26]. These findings are remarkable, because the ASM pathway is critical for edema formation in many models of acute lung injury [27] including neonatal piglet models [28,29] and may also promote apoptosis in lung epithelial cells [30,31]. …”
Section: Introductionmentioning
confidence: 99%